A novel PAX9 mutation causing oligodontia. (December 2017) - Daw, Eiman Mohammed; Saliba, Christian; Grech, Godfrey; Camilleri, Simon
Highlights: An extended family exhibiting both hypodontia and oligodontia is described. Mutations were found in MSX1 and PAX9 genes. The PAX9 mutation is novel and associated solely with the oligodontia phenotype. Abstract: Introduction: An extended family presenting with several members affected by developmentally missing teeth was investigated by analysis of the MSX1 and PAX9 genes. Materials and methods: Saliva samples were collected and DNA extracted. Primers were designed to span the exons and intron-exon junctions of the MSX1 and PAX9 genes. These primers were optimised using gradient Polymerase Chain Reaction. The amplified fragments were sent for Sanger sequencing Results: a novel heterozygote missense mutation in exon 3 of PAX9 (c.296G > C, p.A99P), was found in two severely affected members of the family as well as a potentially pathogenic heterozygote variant (c.119C > G, p.A40G) in exon 1 of the MSX1 gene. Conclusion: The PAX9 A99P mutation is in the DNA binding domain and is predicted to be pathogenic.